Stress in paid and unpaid work as related to cortisol and subjective health complaints in women working in the public health care sector. Issue 4 (7th August 2017) - Blom, Victoria; Svedberg, Pia; Bergström, Gunnar; Mather, Lisa; Lindfors, Petra
Abstract : Purpose: Focusing on 420 women employed within the woman-dominated health care sector, the purpose of this paper is to investigate how any variation in their total workload (TWL) in terms of paid and unpaid work relate to various subjective health complaints (SHC) ( n =420) and the neuroendocrine stress marker cortisol ( n =68). Design/methodology/approach: The authors explored how any variation in their TWL in terms of paid and unpaid work related cross-sectionally to SHC ( n =420), and the neuroendocrine stress marker cortisol ( n =68). Findings: Hierarchical regression analyses showed that stress of unpaid work was most strongly related to diurnal variations in cortisol. Both stress of paid and unpaid work as well as TWL stress, but not hours spent on TWL, were related to SHC. Practical implications: Taken together, objective measures of hours spent on various TWL domains were unrelated to outcome measures while perceptions of having too much TWL and TWL stress were linked to both cortisol and SHC, i.e. how individuals perceive a situation seem to be more important for health than the actual situation, which has implications for research and efforts to reduce individual TWL. Originality/value: This study is unique in showing that unpaid work and perceptions having too much TWL relate to stress markers in women working in the public health care sector.